Lebe Bae Baku Sayang: Moderasi Beragama ala Pemuda Lintas Iman di Kelurahan Honipopu Kota Ambon - Anwar, Ahsani Amalia; Rahayaan, Vitalia; Titawael, Ekmon (Jurnal Riset Agama, 2025)
This study aims to examine the strategic role of interfaith youth in Honipopu Subdistrict, Ambon City, in preserving and promoting the local wisdom of lebe bae baku sayang as a strategy for strengthening religious moderation amidst the challenges of pluralism and a history of socio-religious conflict. Employing a qualitative approach with a case study design, the research draws on in-depth interviews, participant observation, and documentation from the interfaith youth community as primary data sources. The findings reveal that the value of lebe bae baku sayang, which means "better to love one another," is actualized by youth through interreligious activities such as communal service, community empowerment programs, and cultural festivals. These efforts significantly contribute to building social cohesion and reinforcing the peaceful collective identity of Maluku. Theoretically, this study contributes to the development of a religious moderation perspective rooted in local wisdom by emphasizing the role of youth as transformative actors who contextualize traditional values into modern socio-cultural practices. The findings hold important implications for educators, government institutions, and religious organizations in designing multicultural training programs and youth capacity-building initiatives grounded in local values. However, the study is limited by its narrow geographic scope and has yet to explore the internal dynamics of youth communities in depth. Therefore, further research in diverse locations and contexts is needed to enrich the understanding of youth roles in mainstreaming religious moderation in Indonesia.